The structure and evolution of scientific collaboration from the perspective of symbiosis - Liu, Junwan; Ding, Kaiyue; Wang, Feifei; Bu, Yi; J. Maus, Gregory (Malaysian Journal of Library and Information Science, 2019)
This paper introduces a novel quantitative metric called the Symbiosis Degree Index for measuring the degree of symbiosis between subjects, which we apply it to analyzing scientific collaboration patterns between researchers. We study the network characteristics of scientific collaboration based on the resultant published research papers indexed in the Web of Science, considering the role of symbiosis. Analyses through our symbiosis metric of the relationship between a pair of mentor and mentee show substantively distinct ramifications from the “old leads young” model. In a sustained collaboration relationship, young researchers do indeed draw support from mentors’ resources to improve their own level of scientific productivity and influence (as predicted in earlier models), but mentors also benefit by increasing their own productivity in publications. The collaborative symbiosis degree between mentor and mentee changes over time as the relationship matures. In the particular case studied here, even though the mentor’s output decreased later in the relationship, their influence (measured through citations) continued to develop at the same pace through these collaborations. This is intended to demonstrate the potential of the metric to produce new insights on the nature of collaboration.